Integrated-optic array illuminator: a new design for guided-wave optical interconnections. - Liao, T; Sheard, S (1998)
An integrated array illuminator can be used not only as an opticalpower distributor for an array of guided-wave optic devices but also asa key element for guided-wave optical interconnections. We presenta new design for an integrated-optic array illuminator with focusingwaveguide diffractive doublet arrays. This integrated arrayilluminator allows independent optimizations of efficient and uniformoptical power distribution and focusing performance. Furthermore, the device can be fabricated with all-optical lithographic technologyand hence has the advantages of mass production with lowcost.